Georgia : Seizing the Opportunity to Prosper - World Bank (Washington, DC, 2015)
Georgia: Seizing the Opportunity to Prosper suggests a path towards sustainable and shared growth. Georgia s story is associated with three stylized facts: high growth with persistent unemployment currently at nearly 15 percent after 10 years of annual growth that averaged above 5.5 percent; a doing business rank of 8 out of 189 countries achieved without recovery to 1990 levels of per capita income suggesting a relatively difficult transition experience in spite of noteworthy success with several governance and business environment reforms; and obstinate socio-economic vulnerabilities reflected in Georgia s status as one of the poorest countries in the Europe and Central Asia (ECA) region of the World Bank with a relatively weak performance on reducing poverty and inequality. Georgia is well positioned to achieve its development objectives. The main challenge is persistent joblessness, which must be addressed to establish a sustainable basis for the pro-poor development model outlined in the Government s Socio-Economic Strategy 2020. This report, which is anchored in the Government s Socio-economic Development Strategy 2020, explores the potential for improved export competitiveness to strengthen employment growth in Georgia and is intended to inform a policy agenda mainly focused on the demand side of the labor market.